From discomfort to collaboration: teachers screening cellphilms in a rural South African school - MacEntee, Katie; Mandrona, April (Faculty of Education, University of the Free State, 2015)
South Africa continues to contend with an HIV pandemic. Teachers have the potential to address prevention and treatment with their learners but they struggle to implement HIV and AIDS education. Cellphilm projects—using cellphones to create videos, and then screening these—is one example of how digital technology can be used to address barriers to teacher-implemented HIV education. In this article we focus on the work of nine teachers who screened their cellphilms to three youth audiences. We explore how teachers can integrate cellphilm screenings into their teaching practice to address HIV and AIDS, and we consider what this integration tells us about the potential and challenges of teachers dealing with this issue in rural South Africa. Informed by a framework of discomfort, we analyse participant observation notes, fieldnotes, and pre- and post-event interviews. We argue that moments of discomfort during the events reveal the difficulties and strategies that teachers use to negotiate multiple—sometimes contradictory—sexual health education policies. The cellphilm screening events provided an opportunity for teachers and youth to learn from each other, even as it contributed to a more nuanced response to the teaching that addresses HIV and AIDS.
Keywords: Cellphone videos; HIV and AIDS; Participatory visual methodologies; Pedagogy of discomfort; Rurality; South Africa